Peroxisome Proliferator-Activated Receptor-γ Antagonizes LOX-1-Mediated Endothelial Injury by Transcriptional Activation of miR-590-5p. (1st July 2019) - Xu, Lei; Zhao, Gang; Zhu, Hong; Wang, Shijun; Sun, Aijun; Zou, Yunzeng; Ge, Junbo
Abstract : Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is one of the major receptors expressed on the endothelium of arterial wall with a key role in endothelial dysfunction and the development of atherosclerosis. Recent evidence suggested that LOX-1 is upregulated under the condition of insulin resistance and could be suppressed by the antidiabetic drugs. We previously also confirmed that Thiazolidinedione (TZD) has the inhibitory effect on LOX-1 in ox-LDL-induced endothelial cells. However, the underlying mechanism is unclear. Here we showed that Rosiglitazone treatment significantly attenuated the expressions of LOX-1, ICAM-1, VCAM-1, p 4 7 p h o x, and the atherosclerotic lesions in ApoE -/- mice with high-fat diet. In vitro, we revealed that Rosiglitazone inhibited LOX-1 by regulating miR-590-5p. Ox-LDL-mediated ICAM-1, VCAM-1, andp 4 7 p h o x were significantly reduced by Rosiglitazone, but all reversed after pretreating the cells with antagomiR-590-5p. Induction with Rosiglitazone activated PPAR- γ and promoted its nuclear translocation in cultured human umbilical vein endothelial cells (HUVECs). The nuclear PPAR- γ upregulated the miR-590-5p level through binding to its transcriptional promoter region. Retaining PPAR- γ in cytoplasm by transfecting withP P A R - γ ⊿ N L S plasmid in HUVECs failed to activate miR-590-5p. Mutation of the promoter region of PPAR- γ also reduced the miR-590-5p promoter luciferase activity. Collectively, these data indicated that PPAR- γ may have the therapeutic potential in atherosclerosis via the transcriptional regulation of miR-590-5p in endothelial cells.